SISALv3: a global speleothem stable isotope and trace element database - Kaushal, Nikita; Lechleitner, Franziska Anna; Wilhelm, Micah; Azennoud, Khalil; Bühler, Janica C.; Braun, Kerstin; Ait Brahim, Yassine; Baker, Andy; Burstyn, Yuval; Comas-Bru, Laia; Fohlmeister, Jens; Goldsmith, Yonaton; et al. (Earth system science data, 2024)
Palaeoclimate information on multiple climate variables at different spatiotemporal scales is becoming increasingly important to understand environmental and societal responses to climate change. A lack of high-quality reconstructions of past hydroclimate has recently been identified as a critical research gap. Speleothems, with their precise chronologies, widespread distribution, and ability to record changes in local to regional hydroclimate variability, are an ideal source of such information. Here, we present a new version of the Speleothem Isotopes Synthesis and AnaLysis database (SISALv3), which has been expanded to include trace element ratios and Sr isotopes as additional, hydroclimate-sensitive geochemical proxies. The oxygen and carbon isotope data included in previous versions of the database have been substantially expanded. SISALv3 contains speleothem data from 365 sites from across the globe, including 95 Mg/Ca, 85 Sr/Ca, 52 Ba/Ca, 25 U/Ca, 29 P/Ca, and 14 Sr-isotope records. The database also has increased spatiotemporal coverage for stable oxygen (892) and carbon (620) isotope records compared with SISALv2 (which consists of 673 and 430 stable oxygen and carbon records, respectively). Additional meta information has been added to improve the machine-readability and filtering of data. Standardized chronologies are included for all new entities along with the originally published chronologies. Thus, the SISALv3 database constitutes a unique resource of speleothem palaeoclimate information that allows regional to global palaeoclimate analyses based on multiple geochemical proxies, permitting more robust interpretations of past hydroclimate and comparisons with isotope-enabled climate models and other Earth system and hydrological models. The database can be accessed at https://doi.org/10.5287/ora-2nanwp4rk (Kaushal et al., 2024).